Producción de etanol a partir del mucílago de cacao (theobroma cacao) mediante fermentación alcohólica. - Luna Calderón, Tania Annabel (Machala : Universidad Técnica de Machala, 2018)
The objective of the present investigation was to obtain ethanol from the cocoa mucilage (Theobroma cacao) above by means of alcoholic fermentation, in order to take advantage of and give an added value to this byproduct, which is discarded due to the lack of knowledge of many producers. cacaoteros of Ecuador. The characterization of cocoa mucilage was determined by physical-chemical analysis such as: pH by potentiometry, Total Acidity by Volumetry, Total Solids and Ash by Thermogravimetric method, Brix by Refractometry, Reductive Sugars by means of the 3,5-dinitrosalicylic acid method , fermentable sugars by high performance liquid chromatography (HPLC) and an elemental analysis using an elemental analyzer (Nitrogen, Carbon, Hydrogen, Sulfur) to know its composition with accuracy. The cocoa mucilage was obtained under aseptic conditions by squeezing fresh cocoa beans into Mayas. After filtration, the mucilage was sterilized at 121 ° C for 15 minutes in order to eliminate any microbial load. The fermentation process was carried out in an amber glass bottle sealed by a natural cork stopper in which the mucilage was added, for a few minutes nitrogen gas was bubbled and finally the yeast inoculum was placed. This process was carried out for 7 days at different stable temperatures of 25 ° C performed in an incubator, 30 ° C in a stove and 28 ° C in the environment, using the freeze-dried commercial yeast Saccharomyces cerevisiae. A control was carried out every 12 hours determining pH, reducing sugars by means of spectrophotometry and the content of ethanol by means of gas chromatography (Column and a flame ionization detector (FID)). The results of the characterization showed that the cocoa mucilage variety above has: 3.76 of pH, 14.95% of Total Solids, 18.11 Brix, 0.27% of Ashes, 1.77% of Acidity, 20.85 % of Reducing Sugars, in the elemental analysis we obtained 0.83% of Nitrogen, 45.92% Carbon, 5.39% of Hydrogen and <0.05% of Sulfur, of fermentable sugars contains: Glucose 62.52 ( gL), Fructose a 63.47 ± 0.05 (gL), Sucrose 45.89 ± 0.05 (gL), Cellobiose 1.52 ± 0.05 (gL). In the production of ethanol, 3 treatments were developed which during the fermentation process reached the following results: Treatment 1 (25 ° C), a pH of 3.91, reducing sugars, 7.089% and 7.39% ethanol; Treatment 2 (28 ° C), a pH of 3.96, reducing sugars 10.216% and 6.48% ethanol; Treatment 3 (30 °) a pH 3.97, of reducing sugars 2.423% and 11.62% ethanol. In conclusion, the cocoa mucilage of the Fino de Aroma variety (Above) represents an ideal substrate for the production of ethanol, and it was also established that treatment 3 is the most effective since it consumed almost entirely the sugars of the cocoa mucilage. , that is to say, it obtained a greater amount of ethanol and in less time, assuming that the production of ethanol besides being linked to the nutritional requirements (mainly nitrogen) of the yeast Saccharomyces cerevisiae is related to the temperature in which said process is subjected, being 30 ° C the optimum temperature of this alcoholic fermentation.
La presente investigación tuvo como objetivo obtener etanol a partir del mucílago de cacao (Theobroma cacao) variedad arriba mediante fermentación alcohólica con el fin de aprovechar y dar un valor agregado a este subproducto, el cual es desechado por muchos productores cacaoteros del Ecuador principalmente por falta de conocimiento del grado de nutrientes y propiedades que posee. La caracterización del mucílago de cacao fue determinada mediante diversos análisis físicos-químicos como: pH mediante potenciometría, acidez total por volumetría, humedad y cenizas por método termogravimétrico, °Brix mediante refractometría, azúcares reductores por medio del método del ácido 3,5-dinitrosalicílico, azúcares fermentables por cromatografía líquida de alta eficacia (HPLC) y un análisis elemental (Nitrógeno, Carbono, Hidrógeno, Azufre) para conocer su composición. La obtención del mucílago de cacao se lo realizó en condiciones asépticas estrujando los granos frescos de cacao en mallas de polietileno, luego de su filtración se procedió a esterilizar el mucílago a 121°C por 15 minutos con el fin de eliminar toda la carga microbiana. El proceso de fermentación se lo llevó a cabo en un frasco de vidrio ámbar sellado herméticamente por un tapón de corcho natural en el cual se adicionó el mucílago, por unos minutos se hizo burbujear gas nitrógeno y finalmente se colocó el inóculo de levadura. Este proceso se lo efectuó durante 7 días a diferentes temperaturas estables de 25°C, 30°C y 28°C efectuada, utilizando la levadura Saccharomyces cerevisiae comercial liofilizada. Se llevó un control cada 12 horas determinando pH, azúcares reductores mediante espectrofotometría y el contenido de etanol mediante cromatografía de gas (Columna y un detector de ionización de llama (FID)). Los resultados de la caracterización mostraron que el mucílago de cacao variedad arriba tiene: 3,76 de pH, 14,95% de Sólidos Totales, 18,11 °Brix, 0,27% de Cenizas, 1,77% de Acidez, 20,85% de Azúcares Reductores, en el análisis elemental se obtuvo un 0,83% de Nitrógeno, 45,92% Carbono, 5,39% de Hidrogeno y < 0,05% de Azufre, de azúcares fermentables contiene: Glucosa 62,52 (g.L), Fructuosa un 63,47±0,05 (g.L), Sacarosa 45,89±0,05 (g.L), Celobiosa 1,52±0,05 (g.L). En la producción de etanol se elaboró 3 tratamientos los cuales durante el proceso de fermentación alcanzaron los siguientes resultados: Tratamiento 1 (25°C) un pH de 3,91, de azúcares reductores un 7,089 % de y 7,39% de etanol; Tratamiento 2 (28°C), un pH de 3,96, de azúcares reductores 10,216% y 6,48% de etanol; Tratamiento 3 (30°) un pH 3,97, de azúcares reductores 2,423% y 11,62% de etanol. En conclusión el mucílago de cacao de la variedad Fino de Aroma (Arriba) representa un sustrato idóneo para la producción de etanol, además se estableció que el tratamiento 3 es el de mayor eficacia ya que consumió casi en su totalidad los azúcares del mucílago de cacao, es decir obtuvo mayor cantidad de etanol y en menor tiempo, asumiendo que la producción de etanol además de estar vinculada con los requerimientos nutricionales (mayormente nitrógeno) de la levadura Saccharomyces cerevisiae tiene relación con la temperatura en la que se somete dicho proceso, siendo los 30°C la temperatura óptima de ésta fermentación alcohólica.
Keywords: THEOBROMA CACAO; MUCILAGO; SACCHAROMYCES CEREVISIAE; ETANOL